2001
DOI: 10.1081/drt-100102909
|View full text |Cite
|
Sign up to set email alerts
|

Drying of Oilseeds

Abstract: Drying of oilseeds is a post harvest operation required for safe storage of harvested seeds. Oilseeds have gained importance in India over the last few years. Fluidized bed (FB) drying and Spouted Bed (SB) drying of oilseeds were studied as potential dryers for these seeds. Experimental pilot fluidized bed dryers were developed and a 2 TPH capacity (mustard seed) FB dryer plant was designed and installed in the lab. Experimental units and a pilot spouted bed dryer were also developed. The dryer units and the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Therefore, drying of seed to low moisture content without loosing its germination requires seed drying at low temperature with dehumidified air. Different studies have been reported for seed drying at low temperature with dehumidified air using either vapour compression dehumidifier (Adapa et al 2002) or desiccant dehumidifier (Danzieger et al 1972;Graham et al 1983;Sturton et al 1983;Kundu et al 2001;Zhangyong et al 2002;Dhaliwal et al 2006Dhaliwal et al , 2009Ondier et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, drying of seed to low moisture content without loosing its germination requires seed drying at low temperature with dehumidified air. Different studies have been reported for seed drying at low temperature with dehumidified air using either vapour compression dehumidifier (Adapa et al 2002) or desiccant dehumidifier (Danzieger et al 1972;Graham et al 1983;Sturton et al 1983;Kundu et al 2001;Zhangyong et al 2002;Dhaliwal et al 2006Dhaliwal et al , 2009Ondier et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Similar study for drying of corn and soybean seeds have been reported by Danzieger et al (1972) and Zhangyong et al (2002), respectively. Kundu et al (2001) carried out investigations on sorption drying of mustard, sunflower, soybean and groundnut oilseeds in fluidized bed of seeds and silica gel under different conditions of drying air temperature, bed height, feed rate, initial moisture content and flow rate of hot air. The drying results were found to be satisfactory based on drying kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, for oilseed processing, fluidized-bed dryers have been used for drying, cooling, dehulling, improving organoleptic properties, and enhancing the storage life and the ease of incorporation into breakfast cereals and ready-to-eat foods (Tosi et al, 1999;Venkatesh Murthy et al, 2008). Previously, Kundu et al (2001) modeled drying kinetic data for fluidized-bed drying of different oilseeds (mustard seed, sunflower, soybean, and groundnut), focusing on enhancing the storage life of these agroproducts. Tosi et al (1999) reported the decrease of nonhydratable phosphatides in soybean crude oil, as a consequence of phospholipase D inactivation by the fluidized-bed technique.…”
Section: Diverse Roasting and Oil Extraction Methods Have Been Reportedmentioning
confidence: 99%
“…Previously, Kundu et al. (2001) modeled drying kinetic data for fluidized‐bed drying of different oilseeds (mustard seed, sunflower, soybean, and groundnut), focusing on enhancing the storage life of these agroproducts. Tosi et al.…”
Section: Introductionmentioning
confidence: 99%